Use of Computed Tomography-Guided Percutaneous Biopsy of Invasive Non-Mucinous Lung Adenocarcinoma to Predict the Degree of Histological Differentiation. (June 2022) - Liu, Dehao; Chen, Lichun; Wang, Xiaoping; Lin, Yikai; Gu, Jianwei
Background: The International Association for the Study of Lung Cancer (IASLC) published a grading system for invasive pulmonary adenocarcinoma that is closely associated with prognosis. This study aimed to investigate the accuracy of computed tomography (CT)-guided biopsy specimen grading and surgery-guided grading systems for detecting invasive non-mucinous lung adenocarcinoma and to determine whether CT-guided biopsy can predict the degree of histological differentiation. Methods: In total, 130 patients with invasive non-mucinous lung adenocarcinoma who underwent CT-guided biopsy before surgical excision were retrospectively studied. Biopsy and surgical specimen pathologies were compared. Grading was performed according to different subtypes proposed by the International Association for the Study of Lung Cancer. Sensitivity, specificity, positive and negative predictive values (PPV/NPV), and accuracy were calculated for each subtype and grade. Results: The concordance rates of biopsy and surgical pathology subtypes and grades were 73.1% and 72.3%, respectively. Sensitivity, specificity, PPV, NPV, and accuracy of grade 3 were 54.8%, 100%, 100%, 87.6%, and 89.2%, respectively. Pathology grades were primarily discrepant with respect to two aspects of biopsy and surgical samples in the same patient. First, the biopsy and surgical specimen pathology findings indicated lepidic and acinar subtypes as the main subtypes in the same patient, respectively. Second, biopsy specimen histology did not find solid types; however, >20% of solid subtypes were identified in surgical pathology samples in the same patient. Conclusions: The preoperative CT-guided biopsy specimen grading system showed relatively high accuracy and could predict the prognosis of invasive non-mucinous lung adenocarcinoma.